Berkenalan dengan Andrew Rippin, Spesialis Kajian Sejarah Tafsir Al-Qur’an - Mardhatillah, Masyithah (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2016)
Andrew Rippin is one of contemporary orientalists who is interested in Islamic teaching as well as its implementation in Muslim’s daily life. He focuses on development of tafsir in Islamic society especially the modern period with its basic assumptions and exegesis result which are, in some degree, different enough with what traditional exegete understood about Qur’an. Unlike most of traditional orientalists, Rippin seemed to be academically fair and neutral in revealing and analyzing the data related with his concern. Additionally, he tended to map the data under some categories he made and not interested in making any comment about the data including agreement, complement or critique as well. Unfortunately, Rippin is not still well-known as other modern orientalists that this paper is trying to introduce little thing about him and his academic findings on Islami, Qur’an, Qur’anic exegesis and contemporary Muslim word including its exegetical traditions.Keywords: Andrew Rippin, Sejarah Tafsir Al-Qur’an, Tafsir Al-Qur’an modern.